(untitled) (Journal of the Management Sciences, 2025)
Strategic risk management is a systematic framework for identifying and addressing uncertainties that could impact an organization’s ability to achieve its long-term objectives, thereby enhancing resilience and ensuring operational continuity. This study evaluated the effect of strategic risk management on the sustainability of construction firms in South-East Nigeria, focusing on five key practices and their corresponding sustainability dimensions which are: the effect of risk monitoring on supply chain resilience, risk identification on operational efficiency, risk mitigation on resource conservation, risk communication on stakeholder engagement and also the effect of risk compliance on quality management sustainability. Utilizing a descriptive survey research design, data were collected from 313 employees across 25 purposively selected large-scale construction firms and analyzed using simple linear regression. The findings revealed statistically significant positive relationships across all tested variables. Risk monitoring was found to have a significant effect on supply chain resilience, explaining 21.3% of the variance (R² = .213, F(1, 311) = 83.941, p = .024). Risk identification significantly influenced operational efficiency sustainability, accounting for 18.9% of its variability (R² = .189, F(1, 311) = 72.316, p = .031). The study concluded that strategic risk management is an indispensable driver of long-term sustainability for construction firms in the region. It is recommended that firm leaders implement formal, enterprise-wide SRM frameworks, and that policymakers create incentives to promote the adoption of these vital practices to enhance industry resilience and performance.